Avoidant/restrictive food intake disorder and autism spectrum disorder: clinical implications for assessment and management. (17th August 2021) - Farag, Fadila; Sims, Annemarie; Strudwick, Katy; Carrasco, Janette; Waters, Amy; Ford, Vicki; Hopkins, Julia; Whitlingum, Gabriel; Absoud, Michael; Kelly, Veronica B
Abstract : Aim: We examined clinical and neurodevelopmental presentations of children with avoidant/restrictive food intake disorder (ARFID) to inform clinical assessment and management. Method: Five hundred and thirty‐six patients (mean age 6y 10mo, SD 3y 5mo, range 10mo–20y; 401 males, 135 females) seen by the tertiary multidisciplinary feeding service at the Evelina London Children's Hospital between January 2013 and June 2019 were included in this case–control study. These children experienced significant feeding difficulties impacting nutrition, development, and psychosocial functioning requiring tertiary specialized input. Data on ARFID diagnosis, demographics, comorbidity, and nutrition was extracted from electronic patient records. Results: Forty‐nine per cent of children met ARFID criteria. The remaining participants had other difficulties including feeding, medical, and/or neurodevelopmental conditions. ARFID is more prevalent among younger patients (4–9 years) and in children with comorbid autism spectrum disorder (ASD). Younger age, comorbid ASD, and male sex significantly predicted ARFID. Diet range and male sex significantly predicted nutritional inadequacy, while comorbid ASD did not. A trend was seen between younger age and nutritional inadequacy. Interpretation: Young children with ARFID should raise suspicion for ASD. Although significant nutritional deficiencies are common in children with comorbid ARFID and ASD, they are correctable with nutritional supplementation. Specialty perspective potentially limits generalizability of findings to community feeding services. We also emphasize the importance of early identification of nutritional deficits and management.